Optimization of corticosteroid induced osteoporosis in ovariectomized sheep - Klopfenstein Bregger, M. D.; Schawalder, P.; Rahn, B.; Eckhardt, C.; Schneider, E.; Lill, C. (Veterinary and Comparative Orthopaedics and Traumatology, 2007)
During osteoporosis induction in sheep, side effects of the steroids were observed in previous studies. The aim of this study was to improve the induction regimen consisting of ovariectomy, calcium/vitamin D- restricted diet and methylprednisolone (-MP)- medication with respect to the bone metabolism and to reduce the adverse side effects. Thirty-six ewes (age 6.5 ± 0.6 years) were divided into four MP-administration groups (n=9) with a total dose of 1800 mg MP: group 1: 20 mg/day, group 2: 60 mg/ every third day, group 3: 3x 500 mg and 1x 300 mg at intervals of three weeks, group 4: weekly administration, starting at 70 mg and weekly reduction by 10 mg. After double-labelling with Calcein Green and Xylenol Orange, bone biopsy specimens were taken from the iliac crest (IC) at the beginning and four weeks after the last MP injection, and additionally from the vertebral body (VB) at the end of the experiment. Bone samples were processed into stained and fluorescent sections, static and dynamic measurements were performed. There were no significant differences for static parameters between the groups initially. The bone perimeter and the bone area values were significantly higher in the VB than in the IC (Pm: 26%, p<0.0001, Ar: 11%, p<0.0166). A significant decrease (20%) of the bone area was observed after corticosteroid- induced osteoporosis (p<0.0004). For the dynamic parameters, no significant difference between the groups was found. Presence of Calcein Green and Xylenol Orange labels were noted in 50% of the biopsies in the IC, 100% in the VB. Group 3 showed the lowest prevalence of adverse side effects. The bone metabolism changes were observed in all four groups, and the VB bone metabolism was higher when compared to the IC. In conclusion, when using equal amounts of steroids adverse side effects can be reduced by decreasing the number of administrations without reducing the effect regarding corticosteroid- induced osteoporosis. This information is useful to reduce the discomfort of the animals in this sheep model of corticosteroid-induced osteoporosis.
Keywords: Osteoporosis; animal model; sheep; corticosteroids; bone histomorphometry